Generations of Computer - Sharma, Nonika; Kaul, Rashika (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
In our research paper we are going to focus on 2G, 3G, 4G generation systems and their standards. Also we will focus on the various advantages and disadvantages of each generation system. We will also study about the various technologies used in each generation system.